Intra-Sentential Switching Found in Maudy Ayunda's Instagram Caption - Clara Ni Kadek Ririn Julitayanti; I Made Yogi Marantika (Journey: Journal of English Language and Pedagogy, 2023)
The objective of this study to examine the intra-sentential switching and the reasons for it in the Instagram captions of Maudy Ayunda. The study employs a qualitative method to present the collected data. The Poplack (1980) theory was applied to categorize the different types of code-switching, and Hoffman's (1991) theory was used to explain why code-switching appeared in the data. In this study, observation is the primary mode of data collecting, with techniques involving reading, note-taking, and classification. This study discovered 24 intra-sentential switching in Maudy Ayunda's Instagram captions. In these captions, language switching occurs within a single sentence. Sentences in another language are used to emphasize or clarify the intended message. Moreover, the study identifies five reasons for code-switching. The highest frequently found reason for code-switching is to be emphatic about something. This often happens in captions where sentences or words are used to convey her opinions. Maudy Ayunda frequently portrays her agreement or disagreement regarding a product, an issue, other people's opinions, and more through her Instagram captions